Disaster mental health and crisis stabilization for children - Baggerly, Jennifer; Microtraining Associates ([Framingham, MA] : Microtraining Associates, 2007)
Video discusses the impact of disaster and crisis on children, guiding principles, basic grounding and containment skills, initial individual interventions and group interventions
Title from title screen
Executive producer, Allen Ivey ; videographer, Greg Curtis ; video editor, Jean-Rene Rinvil
Presented by Jennifer Baggerly
Keywords: Child disaster victims -- Mental health; Post-traumatic stress disorder in children; Crisis intervention (Mental health services); Disasters -- Psychological aspects